TURN TAKING STRATEGIES BY EQWIP HUBS COMMUNITY - Auzy Andria Umar; Lisetyo Ariyanti (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This study discusses the turn taking strategies in conversations. . The purpose of turn taking is to analyze the way the participants and the speakers deliver their argument into conversation  using turn taking strategies. This study using qualitative research . The source of the data is the transcription of the participants’ dialogue during their discussion. This study using the turn taking strategies which is used by the participants and to analyze the reasons behind the conversation. the main issues in this research are ; What turn taking strategies are used by the participants in Eqwib Hubs community? And  Why do the participants use those turn taking strategies. the results of this study showed the interaction of the use of "turn taking" which is dominated by participants who feel curious about the conversation and also become aware of what strategies are most often used by the participant and the speaker.   Keywords : Turn taking , Conversation analysis , discourse analysis.